La asignación económica por hijo discapacitado a cargo en el sistema español de Seguridad Social - Areta Martínez, María (Revista de Derecho, 2019)
Article 39.1 in the Spanish Constitution of 1978 entrusts public authorities with themission to ensure the social, economic and legal protection of the family. Within thisconstitutional framework, the Spanish government approved the Comprehensive Planto Support the Family (2015-2017) on the 14th May 2015. This plan is structuredalong seven strategic lines, the first of which is the socio-economic protection of thefamily. One of its specific measures consists of studying the improvement of benefitsfor dependent children or minors in foster care.The allowance for a dependent child or foster child is a family benefit under theSpanish Social Security System. It is non-contributory [Article 86.2.b Royal LegislativeDecree No 1/1994] and therefore doesn’t require a beneficiary to pay social securitycontributions as it is sustained by general taxation. Currently Article 181.a of the RoyalLegislative Decree No 1/1994 and Article 3.a of the Royal Decree 1335/2005 governthis allowance. They entitle the recipient to apply for it for each dependent child(biological or adopted) or a minor foster child under 18, whether they are disabledor not. They also allow for each child or dependent over 18 affected by a disabilityof a minimum of 65%.This study doesn’t examine the aforementioned family benefit in its entirety but insteadfocuses on analyzing the legal issues in the case of a dependent disabled child.In particular the study delves into the legal requirements for the disabled child. Onoccasion the author makes some considerations and de lege ferenda proposals. These aremade with the humble intention of trying to improve rules and regulations on thismatter and thereby making progress on the protection of families in general and inparticular for those families with disabled children.
Keywords: Families with disabled children; Spanish Social Security System; child benefit